Penampilan Fenotipik dan Stabilitas Sorgum Manis untuk Bahan Baku Bioetanol - Pabendon, Marcia B.; Mas'ud, S.; Sarungallo, Rosalia S.; Nur, Amin (Jurnal Penelitian Pertanian Tanaman Pangan, 2012)
The objective of this study was to evaluate the phenotypic performance of promising lines sweet stalk sorghum to produce high yield of ethanol different agroecological zones. Eleven genotipes and three check varieties of sweet sorghum were tested in eight different locations in four provinces in Indonesia, namely Sidrap and Bulukumba (South Sulawesi), Polman and Majene (West Sulawesi), Telaga and Biyonga (Gorontalo), and Kendalpayak and Tajiran (East Java) from July until December 2009. The combined analysis of variance showed that the effect of genotypes, locations, interaction of genotipes and locations, were significant for all traits. Based on the phenotypic performance five genotipes with high yield of ethanol were identified. Yield ethanol was high up to 4536 l/ha much higher than those of three check varities. Genotypes Watar Hammu Putih, 4-183A, 15011A, 15011B, and 15021A yielded ethanol from the fermentation process amounted to 6616 l, 4999 l, 5927 l, 5732 l, and 6653 l/ha. The high were ethanol production from each genotype was supported by characters that were relatively different, but the most dominant was the weight of biomass stem per ha, with the coefficient of correlation of 0.92. Stability analysis identified four characters, namely brix sugar content, production of ethanol per hectare, weight of stem biomass, and grain yield per ha. The five promising genotipes with high ethanol yields, were adaptive to spesific loacations. Genotypes 5-193C had wide range of adaptation across the 8 locations, but ethanol production was lower than that check cultivar. Genotype with the highest grain yield was 1090A.